ANALISIS PERLINDUNGAN HUKUM TERHADAP GANTI KERUGIAN AKIBAT INVESTASI ILEGAL - Leonard Arminta; Ariawan Ariawan (Fakultas Hukum Universitas Tarumanagara, 2021)
Crimes in the financial sector continue to emerge, along with various types of new investment methods. In the past people invested their money in property, foreign currency, stocks, gold and bank deposits. but now many people are investing their money into digital money. For example, crypto currency is a development and evolution of digital money. and all investments basically aim to make a profit with the money spent, but when it comes to investment then we must know that all investments have risks. but there is one risk that is worst known as fraudulent investment. where this fraudulent investment deceives its victims by investing in something that doesn't actually exist, so that there will be a time when the investment will be completely lost. and will lead to fraud to all investors on these fraudulent investment. Especially in new types of investments, even now people invest their money in trading robots. And this is triggers a lot of potential crime and fraud in investments. So the protection of laws is the most important things to get compensation in investment fraud activities.